Primary pulmonary synovial sarcoma: a rare case report - Kasturi, Sumalatha; Rendla, Santhosh Babu; Vemula, Sreenivas; P, Shanmuga Raju (International Journal of Research in Medical Sciences, 2017)
Primary lung sarcoma is an extremely rare tumor, accounting for less than 0.5% of all lung tumors. Histological subtypes are differentiated on the basis of immunohistochemical markers, such as vimentin, desmin, actin, CD99, and epithelial membrane antigen. A 50-year-old male presented with progressively increasing shortness of breath with cough for 2 months. On Contrast Enhanced Computed Tomography (CECT) of thorax a large heterogeneous mass with multiple areas of necrosis, occupying almost whole of left hemithorax was seen. CT-guided Fine Needle Aspiration Cytology (FNAC) revealed spindle cell neoplasm. Histopathological examination revealed a spindle cell sarcoma. On immunohistochemistry the tumor cells expressed both epithelial membrane antigen and vimentin. Hence, final impression from immunohistochemistry was primary monophasic synovial sarcoma of lung.